INVESTIGASI SEKTOR UNGGULAN PEREKONOMIAN KABUPATEN LOMBOK BARAT - Dudi Septiadi; Maiser Syaputra; Fariq Azhar; Ahmad Fauzan (Jurnal Ekonomi-Qu, 2021)
Investigation of leading sectors is a strategic effort in planning regional economic development in the future. This research aims to; 1) describe the objective condition of the economic sector of West Lombok Regency; 2) analyze the growth pattern and classification of the economic sector of West Lombok Regency; 3) analyze and map leading sectors to improve the economy in West Lombok Regency. This research was conducted by observing the pattern of development of the structure forming GRDP. The unit of analysis used in this study is the sectoral GRDP structure of West Nusa Tenggara Province as the top region and the sectoral GRDP structure of West Lombok Regency as the bottom region (area of research analysis). The data used in this study is a type of secondary data. Research data sourced from the Central Bureau of Statistics. The observation period is sectoral GRDP from 2016 – 2019.  The research method used in this article is quantitative descriptive analysis. The available data were analyzed using descriptive analysis approach, Klassen Typology analysis and Location Quotient (LQ) analysis. The process of data analysis using Microsoft Excel application. The results of the analysis show that the Agriculture, Forestry, and Fisheries Sector has a contribution of 20.40 percent in forming GRDP with a value of Rp. 2222.29 Billion. Based on the results of the location quotient analysis, there are 12 basic sectors and 5 non-basic sectors. Based on the typology classification analysis, there are two sectors including the Advanced and Fast Growing sectors, namely the water supply, waste management, waste & recycling sector; and the transportation & warehousing sector, where both sectors based on location analysis are included in the basic sector category. Based on the classification typology analysis, the agricultural sector; the trade sector; and the company service sector are relatively lagging sectors, where the three sectors are included in the non-basic sector category.